Privileged minorities: Syrian christianity, gender, and minority rights in postcolonial India - Thomas, S. (Sonja) (Hyderabad: Orient BlackSwan, 2019)
The Syrian Christians of Kerala are considered
Bibliography: p.15
Keywords: Minority Rights - Postcolonial India; Syrian Christianity; Gender Rights - Postcolonial India